A shari'ah evaluation on micro financing products in Islamic banks in Indonesia - Mihajat, Muhammad Iman Sastra (Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2015)
Indonesia is home to the largest Muslim majority financial market in the world, and has a highly complex micro finance and rural finance sector which has evolved over the last century. Interestingly, micro financing services have always accounted for the largest component of financing activities extended by Islamic banking institutions in Indonesia, due to the fact that the majority of Indonesian people are in the middle to low level income category. This study highlights the history and development of micro financing in Islamic Financial Institutions (IFIs) in Indonesia and attempts to evaluate the shariah aspects in micro financing products in Indonesian Islamic banks which covers 7 (seven) Islamic banks and 15 (fifteen) Islamic rural banks (BPRS). There are five major contracts that are used in micro financing products in Indonesian Islamic banks which are murabahah, ijarah, mudarabah, musharakah and rahn. In Indonesia, until June 2012, the murabahah contract still dominated as the instrument of choice for Islamic banks that uses micro financing for MSMEs (Micro, Small and Medium Enterprises) comprising of 56% of the total financing portfolio. Interestingly, the contract of qard (loan without interest) increased significantly from only IDR1.829 trillion in 2009 to IDR12.937 trillion (12%) in 2011. This study discusses and evaluates the shariah compliance of micro financing products in Islamic banks in Indonesia in accordance with the fatwas of DSN-MUI (National Shari'ah Board Indonesian Council of Ulama), Bank Indonesia Regulations (PBI), and classical fiqh doctrines. This study indicates that the majority of micro financing products in Islamic banks in Indonesia comply with Fatwa DSN-MUI and Bank Indonesia Regulations. However, there are some relevant shariah issues that need to be further addressed despite their compliance with sharīcah regulations issued by DSN-MUI and Bank Indonesia, including combination of contracts and selling gold on installment which is clearly prohibited in a hadith of the Prophet Muhammad (pbuh).